2018
DOI: 10.1111/pcn.12805
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of emotional processing assessed with fear conditioning by interpersonal conflicts in patients with depression and schizophrenia

Abstract: Aim While emotional processing is implicated in various psychiatric illnesses, its differences among diagnoses are unclear. We compared associative learning of social values in patients with depression and schizophrenia by measuring skin conductance response to interpersonal stimuli. Methods We included 20 female outpatients each with depression and schizophrenia. They underwent Pavlovian conditioning experiments in response to a classical aversive sound, and an interpersonal stimulus that was designed to caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…Previous researches have reported that patients with schizophrenia do not show differential SCRs to an aversive social stimulus during the acquisition phase, suggesting an intrinsic impairment of the Pavlovian conditioning in associative learning in schizophrenia 23 . Even though they measure the differential SCR to the CS+ and the CS−, we consider it highly interesting to have obtained similar results in our social fear conditioning experiment depending on the level of Cognitive-Perceptual schizotypal personality traits.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous researches have reported that patients with schizophrenia do not show differential SCRs to an aversive social stimulus during the acquisition phase, suggesting an intrinsic impairment of the Pavlovian conditioning in associative learning in schizophrenia 23 . Even though they measure the differential SCR to the CS+ and the CS−, we consider it highly interesting to have obtained similar results in our social fear conditioning experiment depending on the level of Cognitive-Perceptual schizotypal personality traits.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, a recent study reported that positive schizotypal traits were significantly and negatively related to empathy for other’s pain using Evoked Response Potential (ERP) measurements 68 , which is in line with this finding, suggesting a lack of responsivity when watching a person receiving an electric shock. Future studies are needed to further explore the modulation of the SCR during the observational phase of social fear learning experiments by the Cognitive-perceptual factor, and whether the impairments of the Pavlovian conditioning processes are affected in a similar way to what happens in people with schizophrenia with the differential SCR to the CS+ and the CS− 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant fear conditioning is widely recognized as an underlying mechanism in various psychiatric disorders, particularly post-traumatic stress disorder ( 53 ). Fear conditioning is a phenomenon mainly involved in the central nervous system, especially the pre-frontal cortical-amygdala-hippocampal circuit ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, very few studies have investigated extinction learning in depressed patients. In a recent study, Tani et al [33] found slower extinction of a fear response following social aversive conditioning in patients with depression. In contrast, Kuhn et al [34] found enhanced extinction of fear responses in depressed patients, but this study used an instructed extinction manipulation, so it is difficult to evaluate learning from feedback during extinction.…”
Section: Introductionmentioning
confidence: 95%